Cognitive effects of high-frequency rTMS in schizophrenia patients with predominant negative symptoms: results from a multicenter randomized sham-controlled trial - Hasan, Alkomiet; Rietschel, Marcella (Schizophrenia bulletin, 2016)
Cognitive impairments are one of the main contributors to disability and poor long-term outcome in schizophrenia. Proof-of-concept trials indicate that repetitive transcranial magnetic stimulation (rTMS) applied to the left dorsolateral prefrontal cortex (DLPFC) has the potential to improve cognitive functioning. We analyzed the effects of 10-Hz rTMS to the left DLPFC on cognitive deficits in schizophrenia in a large-scale and multicenter, sham-controlled study. A total of 156 schizophrenia patients with predominant negative symptoms were randomly assigned to a 3-week intervention (10-Hz rTMS, 15 sessions, 1000 stimuli per session) with either active or sham rTMS. The Rey Auditory Verbal Learning Test, Trail Making Test A and B, Wisconsin Card Sorting Test, Digit Span Test, and the Regensburg Word Fluency Test were administered before intervention and at day 21, 45, and 105 follow-up. From the test results, a neuropsychological composite score was computed. Both groups showed no differences in any of the outcome variables before and after intervention. Both groups improved markedly over time, but effect sizes indicate a numeric, but nonsignificant superiority of active rTMS in certain cognitive tests. Active 10-Hz rTMS applied to the left DLPFC for 3 weeks was not superior to sham rTMS in the improvement of various cognitive domains in schizophrenia patients with predominant negative symptoms. This is in contrast to previous preliminary proof-of-concept trials, but highlights the need for more multicenter randomized controlled trials in the field of noninvasive brain stimulation.